Effects of EU enlargement on foreign direct investment - Galego, Aurora (2012)
The begining of the transition process in the CEEC witnessed a remarkable increase in FDI flows to the region. Although not equally benefiting all countries, such growth in external investment has been an important source of financing for industry and economic development. In addition, FDI is usually considered the fastest way of transfering intangible assets such as access to international markets, new technologies and also market-oriented business culture to the previously centrally controlled economies. These are especially important, given the plans of EU membership shared by all these countries.Competition to activelly attract FDI has therefore been fierce, becoming one of the driving forces of the structural reforms implemented in these countries to improve investment conditions for foreign firms.A number of studies have focused, both theoretically and empirically, on the motives that lead enterpreneurs to engage in international application of funds, and on the motivesthat make some locations more attractive for certain types of projects than others. At the EU level, reduction of overall risk is probably one critical aspect, since every enlargement has generated a boost of FDI flows to the new members. In the case of the CEEC, however, the transition to a market economy and the prospect of future participation in the EU have, in most cases, a priori triggered the process.In this analysis, robust econometric techniques are employed to model FDI flows, to identify their main determinants, and to try to anticipate future trends of foreign investments in the CEEC and in two of the so-called cohesion countries, Portugal and Spain. the latter is done with the objective of ascertaining diversion of direct investment funds from peripheral EU countries to the CEEC.